Hotel guests' loyalty, behaviour, and service recovery satisfaction based on rating perception - Josimović Milica; Cvjetković Milena; Petrović Radivojević Slavica (Journal of Engineering Management and Competitiveness, 2025)
This paper aims to examine the role of perceived hotel ratings as a mediator of loyalty in the relationship between service recovery satisfaction (SRS) and both the discretionary and dysfunctional behaviour of hotel guests. The research utilised analysis of variance, factor analysis, and structural equation modelling (SEM). The results indicate that perceived hotel ratings have an impact on SRS; specifically, the lower the hotel rating, the greater the impact of SRS on loyalty, and conversely, this is also the case regarding the influence of loyalty on guests' behaviour. Additionally, the findings suggest that the national culture of guests affects both SRS and hotel guest loyalty.